A Study on Diversity and Inclusion: HR Perspective - Snehal Gund; Dr. Diksha Swaroop (International Journal of Engineering and Management Research, 2024)
Diversity and inclusion (D&I) are pivotal in today's global landscape, acknowledging the value of differences to enrich organizational culture and foster innovation. Diversity covers various aspects like race, gender, age, ethnicity, culture etc., while inclusion actively fosters an environment where these differences are respected and valued. D&I plays a crucial role in talent attraction, retention, and employee engagement, contributing to a positive corporate culture that promotes equal opportunities for everyone. The research methodology is descriptive and exploratory, incorporating both primary and secondary data sources to offer a comprehensive perspective on this vital subject. The primary data collection involves the administration of questionnaire to HR professionals from various industries within Vapi and Silvassa region, ensuring diverse perspectives and experiences. This approach allowed for the accumulation of firsthand insights and perspectives directly from those actively engaged in diversity and inclusion practices within their organizations. Complementing the primary data, the secondary data sources included literature review on D&I, delving into evolving definitions, frameworks, and best practices. This multifaceted research design enabled a thorough exploration of the intricate nuances of diversity and inclusion in contemporary workplaces. The research objectives include studying the concept of Diversity and Inclusion, gain insights from HR professionals across various industries, and identifying the challenges organizations face when implementing successful D&I programs. The collection is geographically focused on Silvassa and Vapi, with questionnaires exclusively administered to HR professionals in these locations. It's important to note that the study's findings are confined to organizations within the Vapi and Silvassa regions.